<u>Answer:</u>
Consistent and dependent
<u>Step-by-step explanation:</u>
We are given the following equation:
1. ![3x+6y-12z=36](https://tex.z-dn.net/?f=3x%2B6y-12z%3D36)
2. ![x+2y-4z=12](https://tex.z-dn.net/?f=x%2B2y-4z%3D12)
3. ![4x+8y-16z=48](https://tex.z-dn.net/?f=4x%2B8y-16z%3D48)
For equation 1 and 3, if we take out the common factor (3 and 4 respectively) out of it then we are left with
which is the same as the equation number 2.
There is at least one set of the values for the unknowns that satisfies every equation in the system and since there is one solution for each of these equations, this system of equations is consistent and dependent.
Answer:
b=16
Step-by-step explanation:
Formula~ 1/2*b*h
1/2*15*b=120
7.5b=120
b=120/7.5
b=16
(you can substitute the value to check-i've done it below)
1/2*16*15=?
if you work it out, the ans will be 120, therefore the ans is correct!
Answer:
A. ![h(x)=\sqrt{x-3}](https://tex.z-dn.net/?f=h%28x%29%3D%5Csqrt%7Bx-3%7D)
Step-by-step explanation:
<h3>Step 1: Definition</h3>
The parent function of
is translated to the left when
is positive in the transformation
.
If
is negative, the graph translates towards the left with the distance equal to the value of
.
<h3>Step 2: Implementation</h3>
Here the graph moved 3 units towards the right. This means that
is negative and has the value of 3.
So, plugging that into the parent function for translation, the function becomes:
![h(x)=\sqrt{x-3}](https://tex.z-dn.net/?f=h%28x%29%3D%5Csqrt%7Bx-3%7D)
Answer:
(-1, 3)
Step-by-step explanation:
x - 5y = -16 [Equation 1]
-x + 3y = 10 [Equation 2]
<u>Adding both equations</u>
- x - x - 5y + 3y = -16 + 10
- -2y = -6
- y = 3
- x - 5(3) = -16
- x - 15 = -16
- x = -1
<u>Solution</u> : (-1, 3)
Answer:
Please let me know if your quadratic is
.
And if so your vertex is (-2,2) and your y-intercept is (0,-6)
Step-by-step explanation:
It says vertex so I'm thinking you meant
. Please correct me if I'm wrong.
The vertex form of a quadratic is
. It is called that because it tells you the vertex (h,k).
So if you compare the two forms you should see -h=2 while k=2.
-h=2 implies h=-2.
So the vertex is (h,k)=(-2,2).
To find the y-intercept, set x=0 and find y.
![y=-2(0+2)^2+2](https://tex.z-dn.net/?f=y%3D-2%280%2B2%29%5E2%2B2)
![y=-2(2)^2+2](https://tex.z-dn.net/?f=y%3D-2%282%29%5E2%2B2)
![y=-2(4)+2](https://tex.z-dn.net/?f=y%3D-2%284%29%2B2)
![y=-8+2](https://tex.z-dn.net/?f=y%3D-8%2B2)
![y=-6](https://tex.z-dn.net/?f=y%3D-6)
So the y-intercept is (0,-6).